Peru’s JUNTOS cash conditional transfer program: geographic targeting (2005- 2017) - Carpio, Miguel Ángel (2019)
The document is structured as follows. Section 2 summarizes the geographic expansion of JUNTOS between its introduction in 2005 to 2017, the latest date for which we have information at the time of writing this report. Section 3 describes the main sources of information used for this analysis, including legislative documents pertaining to this program. Section 4 describes the initial eligibility rule and its changes over time based on publicly available information. When appropriate and relevant, we provide a description of the main limitations found in the available information. Section 5 explains the additional assumptions required to replicate the rule and presents the results of the replication exercise. We hope that this report will be useful to the community of scholars and practitioners interested in CCTs generally and JUNTOS specifically.